Children’s Hope: Semiotic Analysis on Atouna El Toufoule’s Video Clip - Dini Anggraheni; Mamdukh Budiman (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
This essay aims to learn more about how children's hope is described in the video clip of Atouna El Toufoule. In the Atouna El Toufoule, several signs have many meanings to represent the actual message and hope of the children. The study of meaning in this article uses qualitative research by analyzing images in the video clip as the primary data. Charles Sanders Pierce's semiotics theory was used to find the real meaning through signs, objects, and interpretants. The results of this study will indicate that signs are motivated mainly by social context and don't require the definition of excessive interpretation. The data takes from the video clip, which shows the side of Palestine’s social life. Interpretants also sometimes directly offer the social life, criticism, social culture, and the situation around them through music. The video clip of Atouna El Toufoule on https://www.youtube.com/watch?v=WpF3hvMhZ1I contains children's hope, moral messages, and an invitation to create peace for children living in the conflict area. The song was translated into three foreign languages (Arabic, France, and English), and it had the purpose of making other countries feel hope.